2005
DOI: 10.7589/0090-3558-41.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and Antibiotic Resistance Patterns of Fecal Indicator Organisms Isolated From Migratory Canada Geese (Branta Canadensis)

Abstract: Thermotolerant fecal indicator organisms carried by migratory waterfowl may serve as reservoirs of antibiotic resistance. To determine the extent to which such antibiotic resistance markers were present in migratory Canada geese (Branta canadensis) on the Maryland Eastern Shore, we isolated Enterococcus spp. and Escherichia coli from fresh feces and examined the antibiotic resistance profiles of these bacteria. Samples were obtained in October 2002, January 2003, and March 2003. Thermotolerant E. coli counts r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 20 publications
7
63
1
3
Order By: Relevance
“…Although determining specific resistance genes for antimicrobial agents was outside the scope of this study, the phenotypic resistance characteristics seen in this study closely parallel previously reported genetic characteristics of Enterococcus. Our isolates also possess the same resistance patterns seen previously from veterinary and environmental sources (Ellerbroek et al, 2004;Middleton and Ambrose, 2005;Macovei and Zurek, 2006). No significant correlation between resistance patterns and the antimicrobial exposure group could be determined in this study, except for chloramphenicol.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Although determining specific resistance genes for antimicrobial agents was outside the scope of this study, the phenotypic resistance characteristics seen in this study closely parallel previously reported genetic characteristics of Enterococcus. Our isolates also possess the same resistance patterns seen previously from veterinary and environmental sources (Ellerbroek et al, 2004;Middleton and Ambrose, 2005;Macovei and Zurek, 2006). No significant correlation between resistance patterns and the antimicrobial exposure group could be determined in this study, except for chloramphenicol.…”
Section: Discussionsupporting
confidence: 50%
“…It has been shown that free-living wildlife, especially waterfowl, may serve as reservoirs, and potentially sentinels, of zoonotic pathogens, most notably Salmonella, Campylobacter, and Escherichia coli (White and Forrester, 1979;Fallacara et al, 2001;Smith et al, 2002;Dobbin et al, 2005;Middleton and Ambrose, 2005). Free-living raptors also are important sentinels for potential pathogens found in their environment (Winsor et al, 1981;Steele et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Com relação a esse Ășltimo antimicrobiano, estudos anteriores jĂĄ observaram que bactĂ©rias da microbiota fecal de aves silvestres apresentavam um Ă­ndice menor de resistĂȘncia a ciprofloxacina (Livermore et al 2001, Middleton & Ambrose 2005.…”
Section: Resultsunclassified
“…VĂĄrios estudos com cepas de bactĂ©rias isoladas de aves silvestres tĂȘm demonstrado altos Ă­ndices de resistĂȘncia a antimicrobianos, mesmo em amostras de animais que provavelmente nunca foram tratados com antibiĂłticos (Livermore et al 2001, Middleton & Ambrose 2005, DeBoer et al 2007, Dolejska et al 2007, Gibbs et al 2007. No Brasil, estudo realizado em Minas Gerais, reportou elevado Ă­ndice de resistĂȘncia bacteriana em amostras oriundas de pĂĄssaros selvagens de vida livre (Nascimento et al 2003).…”
Section: Introductionunclassified
“…are considered the most important bacterial pathogen isolated from migratory quails (Mohamed et al, 2001;Effat and Moursi, 2005). Moreover, the development of antimicrobial resistant strains of zoonotic bacteria constitutes a public health risk, increasing risk of treatment failures (Middleton and Ambrose, 2005).…”
Section: Introductionmentioning
confidence: 99%